MINIMIZING STUDENTS’ MISTAKE IN MAJORS CHOICE: A PHENOMENOLOGY STUDY ON TALENT MAPPING PROGRAM IN SENIOR HIGH SCHOOL STUDENTS - Taufiq Taufiq; Aries Musnandar (Universitas Islam Raden Rahmat Malang, 2018)
This study is an attempt to highlight the function of individual talent mapping towards the success of students’ performance. According to Irine Guntur (2014) about 87% college students in Indonesia were wrong majors choice. The circumstance is the main cause that they cannot be able to occupy most strategic and proper professions in the workplaces. Even, many of them become intellectual unemployment. In order to overcome with this problem the talent mapping method for senior high school students is proposed before entering college or university for further education. The study employs simply a phernomenological research which is the reflective study of prereflective or lived experience. As the alternative qualitative research method to which researchers can turn (Catherine Adam and Max van Manen in Given 2008). Hence, researchers has been involving on talent mapping program in which the results will enable and improve students’ potentials to reach the best learning achievement. The study concluded that talent mapping program is urgently needed for senior high school students before they enter college or university. Therefore, the talent mapping program will enhance to the students’ academic results significantly for getting success in the future life